Western Australia's Local Government Act 25 years on and under review: A qualitative study of local government Chief Executive Officers. Issue 4 (18th February 2021) - Hirst, Tracey M.; Carpini, Joseph A.; Timming, Andrew R.; Notebaert, Lies
Abstract: The Local Government Act 1995 (WA), which prescribes local governments' (LGs) powers and responsibilities in Western Australia (WA), is undergoing a major review. This is likely to have significant impact on LGs and the communities they serve. Qualitative data from 43 (31%) WA LG Chief Executive Officers (CEOs) were obtained and analysed to inform the review. Structural issues emerged across three points of conjunction: the interfaces between (i) state–local government, (ii) councillors–CEO and (iii) councillors–community. The state–local government conjuncture related to the perceived need for state government to address harassment towards LGs and staff. The councillors–CEO interface revealed interconnected issues that predisposed these political–administrative branches to conflict. The principle conflict was the statutory requirement for CEOs to report councillors for legislative breaches (whistleblowing) while depending on councillors for their employment. Other interconnected issues related to the recruitment, performance management, and job security of CEOs and the knowledge, skills, and abilities of councillors regarding human resource management. The councillors–community interface related to the lack of role clarity regarding councillors' responsibilities. Overall, the key concern was the tension at the councillors–CEO interface. Practical recommendations include structural and legislative changes to reconcile identified issues. This research provides useful insights that may improve the functioning of LGs. Abstract : Interviews with LG CEOs revealed eight structural issues to be considered in the review and replacement of the Local Government Act 1995 (WA) relating to the interfaces between state–local government, councillors–CEO, and councillors–community. This research provides useful insights into ways of optimising local government functioning by reconciling points of tension.